Contemporary U.S. Counter-terrorism Strategy toward Somalia - Wood, Molly (Department of Political Studies, 2019)
The United States is involved in strategies of counter-terrorism in many countries around the globe. Al-Shabaab in Somalia has been a United States designated foreign terrorist organisation since 2008. The objective of this dissertation is to determine the nature of contemporary counterterrorism strategy undertaken by the United States toward Somalia and to understand how it has been determined and sustained over time. In order to identify the specific type of counter-terrorism strategy applied to that country, a typology of four counter-terrorism strategies undertaken by the United States toward other countries has been developed. The secondary but closely related question this dissertation attempts to answer is which determinants, or factors, have caused a shift or change in the United States counter-terrorism strategy in Somalia. By identifying determinants that affect strategy, the justification for a change, shift, or stayed course in strategy is made clearer. The typology and key determinants were initially assessed beyond Somalia to include insights from United States involvement in countries such as Vietnam and Afghanistan. This dissertation contends that that the United States has been engaged in the same counter-terrorism strategy against al-Shabaab since the early days of its re-engagement in the Somali conflict. Applying the typology to situational analysis dating back to as early as 2002, it becomes clear that the United States employs and has maintained a complex/combined counterterrorism strategy toward Somalia. In fact, the research conducted for this dissertation supports the overall argument that complex/combined counter-terrorism strategy is especially broad, which enables the United States to prioritise a light military footprint and low costs of involvement in combating al-Shabaab without becoming heavily involved. The malleable nature of this strategy allows the United States to shift resources and tactics with relative ease.